Visual grammar as a prescriber for the social storytelling in advertising: A creative analysis approach based theoretical approaches to photography - Viñas Limonchi, Manuel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The present paper offers a new take on various procedures and visual argumentative strategies that favor the interpretative transition found in the persuasive strategies of advertising and informative column writing. This analysis is centered on the appearance and narrative of one of the many ad campaigns that Oliviero Toscani carried out for Benetton and deconstructs the explicit aspects of the image used in the communicative process. To do so, the article relies on the praxis of photography as well as a qualitative approach that seeks to document in a reflexive and visual manner the reality that affects society.